Shopgirls : a novel - Blau, Jessica Anya (Mariner Books, 2025)
"Nineteen-year-old Zippy can hardly believe it: she's the newest and youngest salesgirl at I. Magnin, "San Francisco's Finest Department Store." Every week, she rotates her three spruced-up Salvation Army outfits and Vaseline-shined pumps; still, she's thrilled to walk those pumps through the employee entrance five days a week as she saves to buy something new. For a girl who grew up in a one-bedroom apartment above a liquor store with her mother and her mother's madcap boyfriend, Howard; a girl who wanted to go to college but had no help in figuring out how; I. Magnin represents a real chance for a better and more elegant life. Or, at the very least, a more interesting one. Zippy may not be in school, but she's about to get an education that will stick with her for decades. Her fellow salesgirls (lifetime professionals) run the gamut from mean and indifferent to caring and helpful. The cosmetics ladies on the first floor share both samples and advice ("only date a man with a Rolex"); and her new roommate, Raquel, an ambitious lawyer, tells Zippy she can lose ten pounds easy if she joins Raquel in eating only every other day. Just when Zippy thinks she's getting a handle on how to be an adult woman in 1985, two surprises threaten both her sense of self and her coveted position at I. Magnin. Set in the Day-Glo colors of 1980s San Francisco, Shopgirls is an intoxicating novel of self-discovery, outrageous fashion, and family both biological and found"--